A Comprehensive Analysis of the T and B Lymphocytes Repertoire Shaped by HIV Vaccines - Wang, Longlong; Zhang, Wei; Lin, Liya; Li, Xiao; Saksena, Nitin K.; Wu, Jinghua; Wang, Shiyu; Joyce, Joseph G.; Zhang, Xiuqing; Yang, Huanming; Wang, Jian; Wang, I-Ming; et al. (Frontiers in Immunology, 2018)
The exploitation of various human immunodeficiency virus type-1(HIV-1) vaccines has posed great challenges for the researchers in precisely evaluating the vaccine-induced immune responses, however, the understanding of vaccination response suffers from the lack of unbiased characterization of the immune landscape. The rapid development of high throughput sequencing(HTS) makes it possible to scrutinize the extremely complicated immunological responses during vaccination. In the current study, three vaccines, namely N36，N51 and 5-Helix based on the HIV-1 gp41 pre-hairpin fusion intermediate were applied in rhesus macaques. We assessed the longitudinal vaccine responses using high throughput sequencing(HTS), which delineated the evolutionary features of both T cell and B cell receptor repertoires with extreme diversities. Upon vaccination, we unexpectedly found significant discrepancies in the landscapes of T-cell and B-cell repertoires, together with the detection of significant class switching and the lineage expansion of the B cell receptor or immunoglobulin heavy chain(IGH) repertoire. The vaccine-induced expansions of lineages were further evaluated for mutation rate, lineage abundance and lineage size features in their IGH repertoires. Collectively, these findings conclude that the N51 vaccine displayed superior performance in inducing the class-switch of B cell isotypes and promoting mutations of IgM B cells. In addition, the systematic HTS analysis of the immune repertoires demonstrates its wide applicability in enhancing the understanding of immunologic changes during pathogen challenge, and will guide the development, evaluation and exploitation of new generation of diagnostic markers, immunotherapies and vaccine strategies.